Knowledge and practice regarding menstrual hygiene management among the Rohingya refugee adolescent girls in Cox’s Bazar, Bangladesh: A mixed method study - Rakhshanda, Shagoofa; Ahmed, Sahlil; Saidu, Samuel; Nderitu, Christine; Thapa, Basanta; Awal, Abdul; Farnaz, Nadia; Rahman, Atiya; Aktar, Bachera; Faruque, A.S.G. (Emerald Publishing, 2022)
This article was published in the International Journal of Human Rights in Healthcare by Emerald Publishing Limited [Copyright © 2021, Emerald Publishing Limited.] and the definite version is available at: https://doi.org/10.1108/IJHRH-10-2020-0096 The Journal's website is at: https://www.emerald.com/insight/content/doi/10.1108/IJHRH-10-2020-0096/full/html